Islamic vigilantism and women in social media - Zaman, Md. Sayeed Al (Universitas Negeri Yogyakarta, 2021)
In Bangladesh, the number of cyber-citizens has been skyrocketing since the 2010s. Violence against women is also proliferating along with the presence of Islam in public spheres and discourses. Using thematic analysis, this study analyzes the discourse data collected from Facebook, the dominant social media of Bangladesh. The key aim of the research is to find out the bedrock of Islamic vigilantism and verbal aggressiveness against women in social media. Subsequently, three interlinked themes have been explored: women’s religiosity, women’s attire, and women’s virtue. The findings have shown that men mainly capitalize on these three conventional and stereotyped ideas of popular Islam to conduct vigilantism against women in social media, which is most often accompanied by different types of verbal aggressiveness. Further, this study considering deep-rooted misogyny and patriarchy in Bangladesh society argues that these factors might have contributed to directing online vigilantism against women. As little research has been done in this area, this research study would lead to further researches in this area.